Assessment of Social Anxiety in Children and Adolescents With Autism Spectrum Disorder. (March 2014) - Kreiser, Nicole L.; White, Susan W.
<x xml:space="preserve">Abstract</x> Despite the high prevalence of social anxiety in individuals with autism spectrum disorder (ASD), there is little agreement on how to best assess such problems in this population. To inform evidence‐based assessment, we conducted a comprehensive review of research that has assessed social anxiety in children and adolescents with ASD without co‐occurring intellectual disability. Although some evidence in support of the reliability of existing measures exists, there are concerns about inflated estimates of the co‐occurrence of social anxiety because of symptom overlap with ASD diagnostic criteria, and the diagnostic sensitivity of existing measures is questionable. Recommendations for clinical assessment of social anxiety in this population and future directions for research on this topic, including the development of new measures, are provided.